KAJIAN YURIDIS SOSIOLOGI HUKUM TERHADAP SUATU TINDAK PIDANA PEMBUNUHAN - Christofel Mantik; Diana Darmayanti Putong; Janeman Jehezkiel Lanawaang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Basically, the presence of Criminal Legal Protection in the community is intended to provide a sense of security to individuals and community groups in carrying out their daily activities. The sense of security that is meant in this case is a feeling of calm, without any fear of threats or actions that can harm individuals in society. The losses referred to are not only related to losses as we understand losses in civil terms but also include losses to body and soul. The body in this case includes the body which is also related to one's soul, the soul in this case includes feelings or psychological states. So in a sense there are several factors or a theory that made the perpetrators of the murder commit their crimes, including; Provide an explanation that Murder is a Criminal Act and also an unlawful act and can take someone's life.